Pengembangan Aplikasi Managemen Tugas Skripsi (Studi Kasus : Program Studi Teknik Informatika Universitas Trunojoyo Madura) - Ach. Khozaimi; Sigit Susanto Putro; Mujibur Rohman (Universitas Bumigora, 2019)
Thesis is an important thing and always exist in a university. The thesis also as a manifestation of the results of scientific papers of students registered and organized in accordance with the prescribed rules. This time the problems arising from the submission of the thesis at the University of Trunojoyo in general is a process of finding and determining a thesis titles appropriate to ask students and unavailability of data from student thesis systematically arranged and computerized, so that in the manufacture of paper there are many similarities, both in the form of titles and methods that are often used by students, this affects the uniformity of student-made thesis results. With the development of thesis management application using code igniter and cosine similarity framework is expected to evaluate, monitor, and improve the performance of the manual system into a computation system while minimizing similarity and plagiarism and can improve services to students who submit a thesis easily in accordance with the rules applicable in the University of Trunojoyo Madura.